2006
DOI: 10.1016/j.ultsonch.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental quantification of cavitation yield revisited: focus on high frequency ultrasound reactors

Abstract: Acoustic cavitation plays an important role in enhancing the reaction rate of chemical processes in sonochemical systems. However, quantification of cavitation intensity in sonochemical systems is generally limited to low frequency systems. In this study, an empirical determination of cavitation yield in high frequency ultrasound systems was performed by measuring the amount of iodine liberated from the oxidation of potassium iodide (KI) solution at 1.7 and 2.4 MHz. Experiments for determining cavitation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 13 publications
1
26
1
1
Order By: Relevance
“…It was observed that mid-frequency levels (378 and 574 kHz) showed higher efficiency on decreasing the asphaltene content of bitumen as compared to higher frequency levels (860, 992 kHz and 1.1 MHz). There are other studies also showed that at mid-frequency level, there is significant rise in the number of cavities formed resulting higher formation of hydroxyl radicals and consequent disintegration of molecules [11]. Kirpalani and McQuinn [11] compared mid to high-range sonication frequencies for the oxidation of iodide to iodine and reported that cavitation yield increases in mid-range frequency levels as compared to high-frequency range.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that mid-frequency levels (378 and 574 kHz) showed higher efficiency on decreasing the asphaltene content of bitumen as compared to higher frequency levels (860, 992 kHz and 1.1 MHz). There are other studies also showed that at mid-frequency level, there is significant rise in the number of cavities formed resulting higher formation of hydroxyl radicals and consequent disintegration of molecules [11]. Kirpalani and McQuinn [11] compared mid to high-range sonication frequencies for the oxidation of iodide to iodine and reported that cavitation yield increases in mid-range frequency levels as compared to high-frequency range.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the sonication frequencies can significantly affect the cavitation yield, and higher yield was observed at midfrequencies as compared with high frequencies. Note that other studies also reported the enhancement of cavitation yield under different frequencies (Kirpalani and McQuinn 2006;Seymour et al 1997). A comparison of two studies, Entezari and Kruus (1996) performed at 20 and 900 kHz and Seymour et al (1997) at 640 kHz, showed a higher cavitation yield at sonication frequency of 640 kHz compared to 20 and 900 kHz.…”
Section: Effect Of Sonication Frequencymentioning
confidence: 75%
“…Further studies were carried out to observe the effect of these sonication frequencies in heavy oil. Cavitation yield measurements were taken to determine the amount of iodine liberated when potassium iodide solutions at different concentrations were subjected to ultrasound (Kirpalani and McQuinn 2006). Cavitation yield was defined as the grams of iodine liberated per unit power density during the oxidation of potassium iodide by hydroxide and peroxy radicals (Gedanken 2004).…”
Section: Measurement Of Cavitation Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Sato et al (2001) claimed that the parametric decay instability of capillary waves, propagating along the liquid fountain surface, leads in turn to USA. Kirpalani and Toll (2002), Kirpalani and McQuinn (2006) and Suzuki et al (2006), on the other hand, suggested that the presence of cavitating microbubbles in the liquid fountain, which grow and collapse in regions of acoustic energy accumulated and mist released, should be important. In either case, USA mechanism needs to be further elucidated, especially in regard to the mechanism of ethanol enrichment.…”
Section: Introductionmentioning
confidence: 99%